Short-Term Outcomes of KeraSys Patch Graft for Glaucoma Drainage Devices: A Case Series - Kundandeep S. Nagi; Ricardo J. Cumba; Nicholas P. Bell; Lauren S. Blieden; Alice Z. Chuang; Kimberly A. Mankiewicz; Donna Nguyen; Robert M. Feldman (Journal of Ophthalmology)
Purpose. Tube-related exposure is a known complication of glaucoma drainage device (GDD) surgery. Our objective is to report the early (approximately 1 year) tube exposure rate of implants covered with a keraSys (IOP Inc., Costa Mesa, CA, USA) tissue reinforcement graft. Patients and Methods. A retrospective, noncomparative, consecutive case series of 42 eyes with GDD implantation with keraSys patch grafts was performed. Main outcome measurements included patch-related complications: patch exposure, tube exposure, wound dehiscence, and patch migration. Results. Forty-two eyes were followed for an average of 15.24±10.44 months (range 1.0–32.3 months). Four (10%) eyes experienced patch-related complications: two with exposure 8 months postoperatively, one with exposure 13 months postoperatively, and one with exposure 4 weeks postoperatively. Conclusion. The effectiveness of the keraSys patch graft is limited by the higher than expected early exposure rate found in this case series. These results should be confirmed in other studies.